Urinary tract infection in relation to preterm delivery in pregnant women treated at Hospital Santa Rosa, Pueblo Libre, 2019 - Fernández-Ramos, Mayra Alejandra (2022)
Introduction: PAHO (2018) reported that the rate of premature births fluctuated between 5 and 18% and in a study carried out in Lima by Mayta (2017), it determined that of 348 pregnant women with UTI, 13.8% had premature births. For this reason, the aim is to establish the relationship between UTI and preterm delivery, to contribute to secondary prevention and to detect infections in a timely manner through the mother's prenatal controls; as well as helping to reduce the rate of complications and / or perinatal mortality due to prematurity. Objective: To determine the relationship between urinary tract infection and preterm delivery in pregnant women treated at the Hospital Santa Rosa de Pueblo Libre, in 2019. Materials and Methods: It was an observational, non-experimental, descriptive, cross-sectional, correlational and Retrospective, performed on 361 pregnant women with urinary tract infection treated at the Hospital Santa Rosa de Pueblo Libre in 2019. The independent variable is UTI and the dependent variable is Preterm delivery. The technique was documentation through medical records. The instrument was the data collection sheet, validated by experts and processed with the IBM SPSS Statistics version 26 program. Results: Regarding the type of UTI, the highest frequency was low, with 68.3%. On the other hand, 84.6% of those who presented UTI more than 3 times a year, did have preterm delivery; of the patients with high UTI, 96.2% had preterm delivery; Of the patients with a positive urine culture, 92.3% did present preterm delivery. The frequency of preterm delivery was 29.3% and the prevalence was 9.97%. Conclusions: There is a relationship between UTI and preterm delivery, because the Pearson Correlation was 0.7, which indicates that it is a high positive correlation and as p <0.05, the relationship is significant.